'When I get better I will do the test': Facilitators and barriers to HIV testing in Northwest Region of Cameroon with implications for TB and HIV/AIDS control programmes - Nwarbébé Barnabas Njozing; Kerstin E Edin; Anna-Karin Hurtig (Taylor & Francis Group, 2010)
The World Health Organization has recommended collaborative activities between TB and HIV programmes with routine counselling and testing for HIV among TB patients in order to improve the uptake of HIV services. We carried out qualitative research interviews with 21 TB patients in four selected TB and HIV/AIDS treatment centres in the Northwest Region of Cameroon to explore the facilitators and barriers to HIV testing. The desire to be healthy and live longer from knowing one's status inspired by the anticipated support from loved ones, faith in a supreme being, influence and trust in the medical authority, encouraged HIV testing. Men also demonstrated their masculinity by testing, thus portraying themselves as positive role models for other men. Meanwhile, the overwhelming burden of facing both TB and HIV simultaneously, influenced by the fear of disclosure of results, harmful gender norms and practices, fear of stigma and discrimination, and misconceptions surrounding HIV/AIDS deterred HIV testing. However, as a result of conflicting emotional experiences regarding to test or not to test, the decision-making process was not straightforward and this complex process needs to be acknowledged by health care providers when advocating for routine HIV testing among TB patients.